A retrospective analysis of the mortality, and the perinatal risk factors for mortality, of very low birth weight infants admitted to Universitas Academic Hospital over a 2-year period – January 2016 to December 2017 - De Abreu, Nelson Serrao (University of the Free State, 2020)
Background: A rise in preterm deliveries of very low birth weight (VLBW) infants, less than 1 500 grams, is currently introducing a global public health dilemma. VLBW infants are at increased risk for morbidity and mortality. Identifying and addressing perinatal risk factors in order to improve the prognosis of VLBW infants are fundamental. Objectives: The primary objectives of this study were to determine mortality rate and disease profile of VLBW infants admitted into the neonatal unit at Universitas Academic Hospital (UAH). The secondary objective was to determine perinatal factors which impacted the mortality of VLBW infants. Methods: A retrospective analytical cross-sectional study was conducted. Study participants, namely VLBW infants, were identified by making use of admission registries, electronic and paper patient records. This data was then used to identify causes of mortality, and perinatal risk factors that increased the risk of mortality. Results: Mortality of VLBW infants was 25.3%. The main causes of mortality were pulmonary haemorrhage (26.3%), necrotising enterocolitis (20%), multi-organ prematurity (20%) and intraventricular haemorrhage (3.8%). Male gender, low birth weight, low gestational age, no antenatal steroids received, hypothermia, surfactant administration, and the need for ventilation were all factors associated with increased mortality. Metabolic acidosis and hyperlactataemia also demonstrated a strong association with mortality. Conclusion: Survival rates of VLBW infants compare favourably with tertiary hospitals in South Africa and developing countries. Basic interventions, such as improving antenatal care and avoiding neonatal hypothermia, and limiting risk factors associated with pulmonary haemorrhage will minimise the mortality risk. Policy change, regarding admission of infants weighing more than 900 grams to intensive care, should be considered to allow escalation of care to improve survival.
Dissertation (M.Med. (Paediatrics and Child Health))--University of the Free State, 2020
Keywords: Antenatal care; Antenatal steroids; Apgar score; Early neonatal death; Extremely low birth weight infants; Gestational Age; High frequency oscillatory ventilation; Kangaroo mother care; Late neonatal death; Mechanical ventilation; Nasal continuous positive airway pressure; Neonatal; Neonatal mortality rate; Prematurity; Sepsis; Small for gestational age; Surfactant therapy; Very low birth weight infants